Peningkatan Kelancaran Membaca Kalimat Siswa Slow Learner Melalui Guided Reading Berbasis Kontekstual: Improving Sentence Reading Fluency of Slow-Learning Students Through Context-Based Guided Reading - Hasan Setiadi; Ishartiwi Ishartiwi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Sentence reading fluency is a crucial skill that enables students to acquire information and comprehend texts. Two sixth-grade "slow learner" students exhibited difficulties such as halting reading, pronunciation errors, improper prosody, and anxiety during oral reading; their pre-intervention performance scores were below 40%. This study aimed to describe improvements in the learning process and the development of sentence reading fluency in these two students during the implementation of a context-based guided reading approach. The study employed the Kemmis and McTaggart Classroom Action Research model across two cycles, each consisting of six sessions. Data were collected through oral reading tests, observations, documentation, and field notes, and were analyzed using a descriptive-qualitative approach supported by percentage analysis. In Cycle I, Student A achieved a score of 63.3%, and Student B achieved 56.7%. Following intervention refinements—including adjustments to processing time, the use of visual aids and color coding, immediate feedback, and more adaptive scaffolding—performance in Cycle II improved to 80.0% and 76.7%, respectively. Both students met the minimum success indicator of 75%. Observations also revealed improvements in attention, participation, independence, and responsiveness to the learning context, along with reduced reading-related difficulties and anxiety. For the two students studied, reading fluency improved during the implementation of the context-based guided reading series, which incorporated various instructional modifications. However, because the interventions were administered concurrently within the action research design—without a control group—the observed improvements cannot be attributed solely to the guided reading method.